Evaluation of bone regeneration in rat calvaria using combination of enamel matrix derivate and bone graft substitute: a histological, histometric and immunohistochemical study - de Carvalho Reis, Erik Neiva Ribeiro [UNESP]; Bezerra Júnior, Germano de Lelis; de Freitas Silva, Leonardo [UNESP]; Braga Polo, Tárik Ocon [UNESP]; de Amorim, Rayane Aquino; Ponzoni, Daniela [UNESP]; Okamoto, Roberta [UNESP]; Molon, Rafael Scaf de [UNESP]; Faverani, Leonardo Perez; Garcia JÚnior, Idelmo Rangel [UNESP] (Springer Nature, 2025)
PurposeThis study aimed to evaluate the bone repair process of standardized calvaria defects in rats treated with different bone substitute materials.MethodsCritical size bone defects with 7 mm diameter were created in the right parietal bone of forty-eight rats using a trephine burr. The animals were randomly allocated to four different experimental groups according to the materials used to fill the defect, as follow: (1) Autogenous group: defects were filled with autogenous bone; (2) Bio-Oss group: defects were filled with demineralized bovine bone mineral; (3) EMD group: defects were filled with Emdogain®; and (4) EMD + Bone group: defects were filled with a combination of both Bone Ceramic® and Emdogain®. Euthanasia was performed after 30 and 60 days.ResultsHistometric analysis demonstrated for the 30-day period that all groups presented areas of bone neoformation, with the EMD + Bone group showing increased percentage of bone neoformation. For the 60-day period, there was a trend towards greater bone neoformation compared to the 30-day period, with a statistically significant difference between the EMD + Bone vs. Bio-Oss groups (p = 0.036). The percentage of new bone formation was significantly higher in the autogenous group compared to all the others. Moderate immunostaining of osteocalcin was observed in all groups at 30 days, which increased significantly in the 60-day period.ConclusionThis study demonstrated suitable biological properties in the association of Emdogain® with Bone Ceramic®. However, further laboratory studies are needed to evaluate the osteoinductive properties of these materials, as well as their behavior in humans through clinical studies.Clinical trial numberNot applicable.